Improvement of Resistance to Clubroot Disease in the Ogura CMS Restorer Line R2163 of Brassica napus - Jiao Chen; Jiahui Li; Mengya Ma; Bao Li; Yuanwei Zhou; Yongzhong Pan; Youjun Fan; Bin Yi; Jinxing Tu (Plants, 2022)
Oilseed rape (Brassica napus) has significant heterosis and Ogura CMS is a major way to use it. Ogura CMS has the advantages of complete and stable male sterility and easy-to-breed maintainers. Therefore, to breed better restorers has become an important goal for this system. Incidentally, clubroot is a soil-borne disease that is difficult to control by fungicidal chemicals, and it has been the main disease of oilseed rape in recent years in China, severely restricting the development of the oilseed rape industry. At present, the most effective method for controlling clubroot disease is to cultivate resistant varieties. One Ogura CMS restorer line (R2163) has shown much better combining ability, but lacks the clubroot disease resistance. This study was carried out to improve R2163 through marker-assisted backcross breeding (MABB). The resistant locus PbBa8.1 was introduced into the restorer R2163, and we then selected R2163R with clubroot disease resistance. Using the new restorer R2163R as the male parent and the sterile lines 116A and Z11A as the female parent, the improved, new resistant hybrids Kenyouza 741R and Huayouza 706R performed well, providing strong resistance and good agronomic traits. This work advances the utilization of heterosis and breeding for clubroot disease resistance in B. napus.